In-Vitro Study of Antioxidant Activities from Ethanol Extracts of Akar Kuning (Arcangelisia flava) - Suratno Suratno; Muhammad Ikhwan Rizki; Mohammad Rizki Fadhil Pratama (Jurnal Surya Medika (JSM), 2019)
This study aims to determine the antioxidant activity of akar kuning (Arcangelisia flava) stem extract from Central Kalimantan using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. This research includes extraction of simplicia and test of antioxidant activity by DPPH method. Based on the analysis of antioxidant activity on ethanol extract from yellow root plant stem IC50 values of 136.81 ppm were obtained. This IC50 value indicates the antioxidant strength of the yellow root plant stems including in the moderate category. Further research on antioxidant activity in the fraction of akar kuning stems needs to be done to determine the composition of the antioxidant compounds in each solvent.